EFEKTIFITAS TERAPI SEFT (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) TERHADAP PENURUNAN INTENSITAS MEROKOK DI KLINIK BERHENTI MEROKOK UPTD PUSKESMAS KECAMATAN PONTIANAK KOTA - ., Catharine Fristy Blaise (ProNers, 2015)
Background :In 2010, Indonesian were the 3rd countries with the higgest smokersapproximately about 82 milion smokers. Public opinion survey on local regulationsabout the smoking area in 2009 showed 194 respondents (46,2%) consumed in onedays are 32 cigerarres. Psychological intervention like psychotherapy againstsmoking behavior were improved, one of them was the SEFT therapy (SpiritualEmotional Freedom Technique) by using the three problems of physical andpsychological problems one of them was the smoking behavior.Objective : The purpose of this study were to analyze the effectiveness of the SEFTtherapy of reduced the smoking intensity in Klinik Berhenti Merokok UPTDpuskesmas kecamatan Pontianak Kota.Methods : This study was a quantitative with quasi-experimental design with preand post test control group design. Sampling technique was consecutive samplingwith 38 samples devided into 19 interventiond and 19 controls.Results : Based on this study, smoking intensity before and after have a SEFTtherapy obtained the p value = 0,002 (p0,05), which mean the SEFT therapyeffective for reduced the smoking intensity. The results of the analysis a mediandifference before and after have a SEFT therapy in intervention and control groupsobtained the p value = 0,000 (p0,05), which mean a significant difference betweenintervention and control group.Conclusion : The SEFT therapy was effective for reduced the intensity of smoking.The SEFT therapy can be used as an alternative for reduced the intensity ofsmoking.Keyword : SEFT Therapy, Smoking IntensityReference : 48 (2003-2016)